Epidemiology and Clinicopathologic Study of Nonneoplastic Cystic Lesions of the Central Nervous System at a Tertiary Care Center - Mukesh Kumar; Mukta Meel; Nikita Choudhary; Ashok Singh; Kusum Mathur (Indian Journal of Neurosurgery)
Background Nonneoplastic cysts of brain are a diverse group of benign lesions with variable etiopathogenesis. Due to different site and histogenesis, these lesions have wide clinicopathologic spectrum. Objective The study was performed to evaluate epidemiology and clinicopathologic spectrum of nonneoplastic central nervous system (CNS) cysts highlighting the role of histopathology in the diagnosis as well as to compare the data with other institution's data available in literature. Materials and Methods All nonneoplastic CNS cysts reported from January 2013 to June 2020 in the Department of Pathology of Sawai Man Singh Medical College, Jaipur, were retrieved and reviewed. The data were evaluated for age, site, cyst wall lining, nature of cyst contents, and location (intracranial and spinal), using SPSS software version 20.0. Results A total of 255 cases were reviewed with an incidence of 4.96% and an age range of 2 to 74 years with slight male preponderance. Among them there were 157, 34, 26, 24, and 2 cases of epidermoid, arachnoid, dermoid, colloid, and glioependymal cysts, respectively, and 1 case of perineural cyst. Infective cysts were much less common than noninfective cysts, accounting for two cases of neurocysticercosis and hydatid cysts each. All cyst types mainly presented with signs and symptoms of a mass lesion. Conclusion Nonneoplastic cyst mainly presented like a CNS mass lesion with overlapping clinical features, and image finding revealing the key role of histopathological analysis. Epidermoids were the most common type of these cysts in the present series followed by the arachnoid cysts.